(untitled) (Journal of Nepal Geological Society, 2013)
The amounts and their variation of minerals in the present river sediments (PR) and basement rocks (BR) of the Kathmandu Valley were estimated by using the X-ray diffraction (XRD) method, in order to estimate the source of the Kathmandu Basin sediments and to interpret paleoenvironmental and paleoclimatic condition of the past Kathamdu Valley. XRD result of the BR and PR samples roughly correspond along respective parts of the Kathmandu Valley, except calcite (carbonate rocks in the eastern, southern, and western parts). The non-clay minerals are quartz, K-feldspar, plagioclase, mic a, chlorite, calcite, and illite, chlorite, kaolinite, smectite, mixed layer illite-chlorite are detected within the clay fraction of the PR sediments. The clay fraction is < 5 wt % within the PR-sediments. Among non-clay fraction, BR and PR from the north contains more or less equal amount of mica, feldspars and quartz, while those from south, east and west are rich in quartz. Therefore, the amount of silicate minerals in the sediments within the Kathmandu Basin is the key to grasping the provenance of the sediments about northern and the other origin. Chlorite in the PR-North is likely a weathering product of mica because chlorite was not included in the BR-North samples. The chlorite and mica were greater in the lower course of the river from the north than in the upper course of the river. Plagioclase is tends to be poor and K-feldspar is rich in the PR-samples, while the amount of the two feldspar are similar to each other in the BR-samples. This tendency may be due to the difference in stability to weathering between the two feldspars. Calcite was probably dissolved during weathering, erosion, and transportation processes, because calcite included in the BR samples was hardly detected in the PR samples. This mineralogical information is applied to the mineralogical studies in the past basin-fill sediments of the Kathmandu Basin (RB-drill core) and to estimate the source of the sediments and paleoenvironmental and paleoclimatic information on this region. Calcite detected in the past basin-fill sediments of the Kathmandu Basin is an important key mineral showing cold and dry climate within the RB drill core. It can also be used to correlate the strata.